Technical Assistanceon Tax Policy : A Review. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1993)
This paper reviews recent experience of technical assistance on tax policy provided by the Fiscal Affairs Department to a selected but diversified group of countries that differ both in their geographical locations and in the nature of their economies. The review finds in the technical assistance advice both common themes applicable to all countries and special elements designed to address issues unique to a specific country, or a subset of countries. It also attempts to assess, to the extent possible, the policy impacts of such advice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet